IMPLEMENTATION AND EVALUATION OF ESG RISK RATINGS: A CASE STUDY OF PT PERTAMINA HULU ENERGI (PHE) - Sandra Zakiya Dwifitriana; Yudo Anggoro (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
Environmental, Social, and Governance (ESG) performance has become essential for oil and gas companies due to the impact of their operations on the environment, communities, employee safety, and governance. As the upstream subholding of PT Pertamina (Persero), PT Pertamina Hulu Energi (PHE) is expected to implement sustainable practices, making the identification of current ESG risk management and areas for improvement important for the company's competitiveness. This study assesses the implementation of ESG risk management at PHE using the MSCI ESG Ratings methodology, addressing how ESG risk is managed under the MSCI Key Issue Framework and which aspects require improvement. Agency Theory and Stakeholder Theory underpin the research. A qualitative case study method was applied, drawing on sustainability and annual reports, company disclosures, MSCI ESG Assessment documents, and surveys and semi-structured interviews with representatives from Compliance, Human Capital, Environment, Safety, and Supply Chain Management divisions. PHE's performance was assessed across seven MSCI Key Issues, followed by a gap analysis. Results show PHE achieved an MSCI ESG Rating of BBB with an Industry Adjusted Score of 5.4 in 2025, an improvement from the previous year, with strong performance in Community Relations, Biodiversity & Land Use, and Toxic Emissions & Waste. Priority areas for improvement include absolute carbon emission reduction targets, measurable health and safety targets, and greater governance transparency.